Exploring identity construction and livestreaming culture in the films Nerve (2016), “Nosedive” (from Black Mirror, 2016), and Spree (2020) - Momo, Mehjabeen Jahan (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in English, 2023.